2018
DOI: 10.1016/j.toxicon.2018.06.074
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of KIM-1 as an early biomarker of snakebite-induced AKI in mice

Abstract: Acute kidney injury (AKI) is one of the most important complications of bothropic poisoning and its early identification remains challenging. The nephrotoxicity of Bothrops insularis venom (BinsV) was previously described by our research group. In this study, we continued to evaluate the effect of BinsV on kidney function in mice and LLC-MK2 proximal tubule cells, evaluating KIM-1 protein as an early AKI biomarker. Male Swiss mice were inoculated with BinsV intramuscularly and observed for 24 h in a metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Currently, serum Cr, serum Bun, and urine volume are used to evaluate kidney function. However, these indices are extremely limited for the early diagnosis of kidney injury [28] and are easily affected by some nonrenal factors [29]. Serum CYS-C is a cysteine proteinase enzyme inhibitor, and it has low molecular weight and does not bind to proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, serum Cr, serum Bun, and urine volume are used to evaluate kidney function. However, these indices are extremely limited for the early diagnosis of kidney injury [28] and are easily affected by some nonrenal factors [29]. Serum CYS-C is a cysteine proteinase enzyme inhibitor, and it has low molecular weight and does not bind to proteins.…”
Section: Discussionmentioning
confidence: 99%
“…They found significant correlation between AKI stages with the above biomarker levels. Dantas et al demonstrated the rise of urinary kidney injury molecule 1 (KIM-1) in mice within 24 h of envenomation even before the rise of creatinine or any pathological changes in kidney tissue [30]. Further studies are required to check applicability and utility of these biomarkers in real-life clinical settings of snake bite envenomation.…”
Section: Early Prediction Of Snake Envenomation Akimentioning
confidence: 99%
“…Hwang characterized the proteins in human urinary exosomes through LC-MS technology and found that the proteome in the DKD group and the healthy control group had significantly different levels of expression [9]. Dantas et al analyzed the kidney tissue proteins of early DKD rats and found that calmodulin (CaM) and senescence marker protein (SMP) were significantly downregulated compared with healthy controls [10]. Lippi et al used ESI-Q-TOF MS/MS technology to screen and found proteins that were significantly upregulated and downregulated in the development stage of DKD compared with control samples [11].…”
Section: Introductionmentioning
confidence: 99%